Antibacterial mechanism of ε-Poly-lysine against Listeria monocytogenes and its application on cheese. (September 2018) - Lin, Lin; Gu, Yulei; Li, Changzhu; Vittayapadung, Saritporn; Cui, Haiying
Abstract: ε-Poly-lysine ( ε -PL) is widely recognized as a natural antibacterial agent because of its broad spectrum antimicrobial property. However, the mechanism of ε -PL against pathogens at the molecular level has not been yet thoroughly described. This work aimed at investigating the antibacterial activity and mechanism of ε -PL at the molecular level against Listeria monocytogenes . ε -PL exhibited antibacterial activities against L. monocytogenes at a low dosage of 0.1 mg/mL. After ε -PL treatment, the marked change on the morphology of bacterial cells was observed by Transmission Electron Microscopy. The characterization of cell membrane surfaces through electrical conductivity, cell membrane permeability and surface zeta potential was also well documented. The intracellular materials (ATP, DNA and proteins) and intracellular enzymes (AKP, ATPase and β -Galactosidase) were analyzed, which revealed the destructive effect of ε -PL on bacterial cells. SDS-PAGE investigation of bacterial proteins demonstrated that the loss of soluble proteins was obvious as well. Results of respiration metabolism manifested that ε -PL inhibited the Embden-Meyerhof-Parnas pathway and the three key enzymes in this pathway. Nevertheless, the ε -PL has no inhibition effects on Topo I/II. Finally, ε -PL was applied to preserve cheese and showed outstanding antibiotic activity during 15-days storage period at 4 °C and 25 °C. Highlights: ε -Poly-lysine exhibited a destructive effect on cell structure of L. monocytogenes. ε -Poly-lysine had inhibitory effect on physiological metabolism of L. monocytogenes. ε -Poly-lysine showed outstanding antibiotic activity against L. monocytogenes on cheese.